Perlindungan Hukum bagi Pemegang Merek terhadap Pemalsuan Merek Fashion - Ni Made Dwi Ari Cahyani; Anak Agung Sagung Laksmi Dewi; Ni Made Sukaryati Karma (Warmadewa Press, 2021)
Trademark is a form of intellectual property which has a function to increase or smoothen trade in services or goods for those who carry out trade in investment and goods. This study aims to explain legal protection for brand holders against violations of fashion brand counterfeiting and to explain the settlement of legal violations against brand holders who are disadvantaged due to fashion brand counterfeiting. This research uses normative legal research methods, namely doctrinal legal research, also referred to as document library research or document study. The approach used is a statutory and conceptual approach. The data used are primary and secondary legal data sources. The results show that the existing legal protection also applies to brand holders, which is protection provided to legal subjects in the form of both preventive and repressive legal instruments. Legal violations against brand counterfeiting are regulated in Law Number 20 of 2016 concerning Marks and Geographical Indications article 83 paragraph (3), which uses the Commercial court route to become an institution in ending trademark disputes, falsification of famous trademark infringements can be resolved through the criminal legal process and legal channels. civil. Legal efforts to hold brand rights against acts of infringement of Zara's Fashion product brands can file criminal and civil lawsuits against proceedings and / or losses in the dragon court adjusted to the provisions stipulated in article 83.The suggestion is to implement the importance of socializing brand registration for legal protection against Brand holders towards increasing awareness for brand owners to register those used